Evaluasi Penerapan Teknologi Informasi Menggunakan Framework Itil Versi 3 - Yulina Yusuf; Arif Gunarto (Sienna, 2020)
Higher education institutions is right now required to have a Website as an information services for the entire of academic community and also to the public STIE Muhammadiyah Kalianda feels that the use of Website is unsatisfactory so that the implementation still needs improvement. Appropriate and easy methods user in carrying out the measurement of Website perormance absolutely are needed, the process of evaluating the performance of information technology implementation that used is the Framework Information Technology Infrastructure Library which is expected to provide a comprehensive solutions related to organizational and management conditions. From the results of the research, it can be concluded, that the management and services that carried out by STIE Kalianda have been in the level of the defined process